1980
DOI: 10.1128/jcm.12.4.572-575.1980
|View full text |Cite
|
Sign up to set email alerts
|

False no-growth blood cultures in pneumococcal pneumonia

Abstract: The growth of Streptococcuspneumoniae in commercial media containing`4Clabeled substrates was studied experimentally; the results of blood cultures that were positive for S. pneumoniae over a 14-month period were analyzed to explain no-growth but radiometrically positive blood cultures from four patients with clinically diagnosed pneumococcal pneumonia. The growth of S. pneumoniae in aerobic blood culture vials resulted in a chocolate color in the medium. S. pneumoniae grew rapidly in both aerobic and anaerobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…Neither method of data analysis had a P value <0. 1 Both blood culture systems positive. A total of 44 blood specimens were culture positive by both systems, and 49 clinically significant microorganisms were recovered.…”
Section: All Culturesa 2: 1abmentioning
confidence: 99%
“…Neither method of data analysis had a P value <0. 1 Both blood culture systems positive. A total of 44 blood specimens were culture positive by both systems, and 49 clinically significant microorganisms were recovered.…”
Section: All Culturesa 2: 1abmentioning
confidence: 99%
“…Pneumococci are known to be subject to self‐destruct processes in liquid cultures due to autolysins such as N‐acetyl‐muramyl‐ l ‐alanine amidase [3], and therefore are known to be a cause of false‐positive blood cultures, as previously described [4–6]. This phenomenon is associated with delayed subculturing of positive bottles [4,7].…”
mentioning
confidence: 99%
“…It would be of interest to know if a LA test was performed in the case presented by Meesen and colleagues [1], in order to rule out the possibility of false‐positive blood cultures due to autolyzed pneumococci, especially when considering one of the cases reported by Adeniyi‐Jones et al. [4]. The patient, who had a high leukocyte count (145 × 10 9 /L), had four aerobic cultures detected as true false‐positive and another bottle flagged positive with no bacterial growth, but with evidence of pnemococcal autolysis.…”
mentioning
confidence: 99%
“…Moreover, these studies were done before acridine orange staining had been recognized as a useful early screening method (12,14,23). Reports that radiometric culture bottles grew baçteria despite negative growth readings (1,3,5,18) and that some radiometric culture bottles had high radiometric readings in the absence of bacteria (2-4, 17,22,25) further suggested that a controlled comparison with conventional media was needed.…”
mentioning
confidence: 99%